Pro‐inflammatory dopamine‐2 receptor‐specific T cells in paediatric movement and psychiatric disorders. Issue 12 (17th December 2020) - Pilli, Deepti; Zou, Alicia; Dawes, Ruebena; Lopez, Joseph A; Tea, Fiona; Liyanage, Ganesha; Lee, Fiona XZ; Merheb, Vera; Houston, Samuel D; Pillay, Aleha; Jones, Hannah F; Ramanathan, Sudarshini; et al.
Abstract: Objectives: A dysregulated inflammatory response against the dopamine‐2 receptor (D2R) has been implicated in movement and psychiatric disorders. D2R antibodies were previously reported in a subset of these patients; however, the role of T cells in these disorders remains unknown. Our objective was to identify and characterise pro‐inflammatory D2R‐specific T cells in movement and psychiatric disorders. Methods: Blood from paediatric patients with movement and psychiatric disorders of suspected autoimmune and neurodevelopmental aetiology ( n  = 24) and controls ( n  = 16) was cultured in vitro with a human D2R peptide library, and D2R‐specific T cells were identified by flow cytometric quantification of CD4 + CD25 + CD134 + T cells. Cytokine secretion was analysed using a cytometric bead array and ELISA. HLA genotypes were examined in D2R‐specific T‐cell‐positive patients. D2R antibody seropositivity was determined using a flow cytometry live cell‐based assay. Results: Three immunodominant regions of D2R, amino acid (aa)121–131, aa171–181 and aa396–416, specifically activated CD4 + T cells in 8/24 patients. Peptides corresponding to these regions were predicted to bind with high affinity to the HLA of the eight positive patients and had also elicited the secretion of pro‐inflammatory cytokines IL‐2, IFN‐ γ, TNF, IL‐6, IL‐17A and IL‐17F. All eight patients were seronegative for D2R antibodies. Conclusion: Autoreactive D2R‐specific T cells and a pro‐inflammatory Th1 and Th17 cytokine profile characterise a subset of paediatric patients with movement and psychiatric disorders, further underpinning the theory of immune dysregulation in these disorders. These findings offer new perspectives into the neuroinflammatory mechanisms of movement and psychiatric disorders and can influence patient diagnosis and treatment. Abstract : In this study, we report of autoreactive dopamine‐2 receptor (D2R)‐specific T cells in a subset of paediatric movement and psychiatric disorders. These T cells recognised three immunodominant regions of D2R that were predicted to bind with high affinity to HLA class II molecules of patients, and T‐cell activation was associated with the secretion of pro‐inflammatory cytokines. These findings suggest a role for autoreactive T cells in the immune dysregulation of movement and psychiatric disorders.